Improvement of Microalga Biodiesel Production Capacity - Suripto Suripto; Lalu Japa (Jurnal Biologi Tropis, 2020)
This research is directed at developing renewable fuel sources, which are not only environmentally friendly, but also more importantly harvested faster and not competitive with agricultural land. For this reason, the potential oil-producing microalgae need to be explored, because it has fast growth and its cultivation development will not compete in land use with food agriculture. This study aims specifically to determine the types of microalgae producing biodiesel oil that can be isolated from the natural Wallacea in NTB waters, to determine light spectrum treatment and N elimination in microalgae culture which significantly increases the productivity and quality of the biodiesel it produces. Based on the distribution map of potential biofuel-producing microalgae types in NTB waters, samples will be collected from several NTB waters, then the target types of microalgae are isolated and cultured in two systems: a closed system (bioreactor) and an open system (raceway pool) with light spectrum variation treatment and elimination of N in microalgae culture nutrients to increase the productivity and quality of the biodiesel oil produced. Biomass was harvested every 48 hours from the bioreactor and every 4 weeks from the experimental pond. Microalgae biomass was extracted with hexane to produce primary oil. This primary oil usually still has a relatively high viscosity compared to petrodiesel, so it is then trans-esterified with methanol and an acid catalyst to increase the fire point and reduce its viscosity. Oil fractionation is also carried out to sort and determine the composition of saturated, mono-unsaturated and poly-unsaturated fatty acids which greatly determine the biodeasel quality of these microalgae. The biodiesel quality variables to be measured are density, viscosity, flash point, freezing point, solubility in water, vapor pressure, reactivity, physical appearance, odor and toxicity. The result showed that, in the community of marine microalgae from Lombok and Sumbawa Islands consist of 62 species of potential producing-oil microalgae were dominated by Bacteriastrum delicatulum, B. variance, Chaetoceros amini, C. affinis, C. liciniosum, C. lorenzianum, Gyrosigma sp., Nannochloropsis oculata, Nitzchia spp., Oscillatoria sp., Pseudonitzschia spp., and Thalassionema nitzschicoides. Types of oil-producing freshwater microalgae in Lombok Island consist of 19 species of potential producing-oil microalgae, identified with high abundance and dominance, covering Microcystis aeruginosa, M. incerta, Nostoc sp., and Pediastrum boryanum. The oil content of the three species of microalgae, namely Chaetoceros amini, Nannochloropsis oculata, and Nitzchia spp which had been cultured by trietmant were 34, 68, and 46% dry weight, respectively.